Genome Characterization and Phylogenetic Analysis of the First Bovine Rhinitis B Virus Isolate in China - Zhai, Shao-Lun; Xie, Yi-Lun; Zhai, Qi; Wen, Xiao-Hui; Lv, Dian-Hong; Chen, Qin-Ling; Wang, Gang; Wei, Wen-Kang (Frontiers in Veterinary Science, 2021)
Bovine rhinitis B virus (BRBV) is an emerging viral species in the genus Aphthovirus, family Picornaviridae. Studies suggested that BRBV was considered a potential etiological agent of bovine respiratory disease complex (BRDC). BRBV has been reported in the United States, Sweden, Canada, Japan and Mexico. However, little information of BRBV was available in China. In this study, we performed viral metagenomic analysis in a calf with respiratory disease. The results showed high abundance (3.85) of BRBV nucleotide and 248 mapped reads in calf samples. Online BLASTn analysis showed that three contigs of those had highest nucleotide similarity (95%) with one Swedish BRBV isolate (BRBV_SWE1, GenBank accession no. KY432299). To identify genome characterization of the Chinese BRBV isolate (designated CHN1), six couples of overlapping RT-PCR primers were designed according to genome sequences of BRBV_SWE1. Through gene cloning and splicing, we obtained genome information of CHN1, possessing 7465 nucleotides (46.6% G+C). Although CHN1 had highest nucleotide similarity (95.1%) with BRBV_SWE1, one 11-nucleotide (ACATTTGTTGT) deletion occurred in 5’ untranslated region compared to SWE1. Phylogenetic analysis showed that CHN1 clustered together with BRBV_SWE1, and far from other BRBV isolates. This study recorded the first discovery of BRBV infection in China. Further investigation should be made in order to evaluate infection status and epidemiological significance of BRBV in China.